DONGENG ORIGINAL NUSANTARA (DANA) BASED ON STORY BASED LEARNING (SBL) TO IMPROVE THE ABILITY OF TEACHER TEACHERS IN SURAKARTA - Adi, Fadhil Purnama; Mulyono, Hadi; Atmojo, Idam Ragil Widianto; Ardiansyah, Roy (Universitas Sebelas Maret, 2018)
The purpose of this service is to improve the ability of elementary school teachers in realizing enjoyable learning through the development of archipelago dongeng material. The subject of this service is an elementary school teacher in the city of Surakarta. The method used in this service begins the Workshop, Practices, and Implementation. In conducting this training, subjects were asked to work on tests related to the development of fairy tale material. Analysis of the data used is pre-test and post-test. The results of this activity are an increase in the knowledge and understanding of teachers about the development of the archipelago fairy tale teaching materials.